Improving the safety of an uncontrolled road traffic junction a case study of maisammaguda T-junction - R. Prasannakumar, Dr; Naga sai baba, Akella; Ranjith Kumar, V (International Journal of Engineering and Technology, 2018)
Road traffic junctions are potential locations for accidents especially when they are not provided with signal and completely uncontrolled. In the present paper, a T-junction located near Maisammaguda was identified as the study location. It was an uncontrolled road traffic junction with many conflicts and congestion, reducing the safety of students, faculty and other commuters. Near about ten professional colleges are located in this area, with heavy traffic flow during morning and evening peak hours. Traffic volume count was made as per IRC guidelines and signal timings were designed for the proposed signalized T Junction. Detailed phasing and timing plans were also arrived at separately for morning and evening peak hours. It is believed that the proposal if implemented will significantly reduce the number and severity of accidents at this location.Â Â